A very low diffusion Fricke gel dosimeter with functionalised xylenol orange-PVA (XOPVA). (16th October 2019) - Smith, S T; Boase, N R B; Masters, K-S; Hosokawa, K; Asena, A; Crowe, S B; Kairn, T; Trapp, J V
Abstract: A gel dosimeter has been developed utilising a recently reported system for reducing Fe 3+ diffusion in a Fricke gel dosimeter which chelates xylenol orange to the gelling agent poly(vinyl alcohol) (PVA). Formulations were investigated using both gelatin and PVA as the gelling agent, along with the inclusion of glyoxal. The resulting gel had an optical density dose response of 0.0031 Gy −1, an auto-oxidation rate of 0.000 23 h −1, and a diffusion rate of 0.132 mm 2 h −1 which is a significant improvement over previously reported gelatin based Fricke gel dosimeters. The gel was also shown to be energy and dose-rate independent and could be reused after irradiation. Thus, this gel dosimeter has the potential to provide a safe and practical solution to three dimensional radiation dosimetry in the medical environment.